Impact of distance education on academic performance in a pharmaceutical care course - Gossenheimer, Agnes Nogueira; Bem, Tamires; Carneiro, Mára Lucia Fernandes; de Castro, Mauro Silveira (PloS one, 2017)
The objective of this study was to compare the performance of pharmacy students from a Pharmaceutical Care course, taught in both distance education (DE) and campus-based formats using active methodologies. For two semesters, students (n = 82) taking the course studied half the subject in the distance education format and half in person. Questionnaires were applied at the beginning of the semester aimed to outline the demographic profile of the students. Their grade in the course was evaluated to determine their performance. The Module 1 (Information on Medication) average on the campus-based was 7.1225 and on DE was 7.5519, (p = 0.117). The Module 2 (Pharmaceutical Services) average on the campus-based was 7.1595 and on distance education was 7.7025, (p = 0.027*). There was a difference in learning outcomes in the Pharmaceutical Care Course between face-to-face and distant education. Therefore, the student performance was better in the distance education module, indicating distance education can be satisfactorily used in Pharmacy Programs.